Studies on Dimensional Stability and Termite Resistance Capacity of Bamboo (Bambusa Balcooa) after Treatment with Chemicals and Plant Extracts - Borthakur, Runumee D.; Gogoi, P. K. (Indian Forester, 2009)
The North-Eastern region of India is a storehouse of bamboo, where considerable quantity of bamboo is being used without any systematic treatment or being treated traditionally like water submersion, smoking and baking over fire. Durability of bamboo can be enhanced from 3 to 30 years depending upon the preservative chemicals, bamboo species and end uses. Various inorganic/ organic formulations incorporating copper, arsenic, boron, zinc, pentachlorophenol are being used individually or in mixture. The use of arsenic/chromium based compositions and pentachlorophenol is under constant review due to environmental consideration and is slated for phasing out in the future. Hence it may be worthwhile to make a comparative study of the efficacy of plant extracts, traditional and other alternative chemicals like boric acid, phthalic anhydride/ maleic anhydride and copper acetate as dimensional stabilizer and anti-termite agents. The dimensional stability of chemically treated (phthalic anhydride) sample in terms of antishrink efficiency (ASE) was increased by 68.80% at the level of 30.81% weight per cent gain (WPG) and the ASE of plant extract (Chromolaena odorata) treated sample increased by 42.13% at the level of 18.17% weight per cent gain (WPG).